2021
DOI: 10.18332/ejm/138596
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect the traumatic childbirth perceptions of midwifery and nursing students: The case of Turkey

Abstract: INTRODUCTION Birth is a natural and joyful situation as well as a process that contains surprise situations that do not go well. Caregivers at birth are affected by this process. Especially when faced with difficult births, it can have an intense psychological effect and a perception of traumatic birth can occur. Although there is research about midwives on this subject, there are very few studies about students who are becoming midwives. The aim of this study was to determine the factors that aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…The traumatic childbirth perception levels of those who had a fear of childbirth and defined childbirth as a difficult and painful process were significantly higher than those who did not. 15 Although Toohill et al found no significant relationship between professional exposure to traumatic childbirth events and high levels of childbirth fear in Australian midwives, it is noteworthy that 90% of those with high levels of fear of childbirth indicated they had experienced trauma in their work. 7 The traumatic childbirth experience of the midwife may increase their fear of childbirth.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The traumatic childbirth perception levels of those who had a fear of childbirth and defined childbirth as a difficult and painful process were significantly higher than those who did not. 15 Although Toohill et al found no significant relationship between professional exposure to traumatic childbirth events and high levels of childbirth fear in Australian midwives, it is noteworthy that 90% of those with high levels of fear of childbirth indicated they had experienced trauma in their work. 7 The traumatic childbirth experience of the midwife may increase their fear of childbirth.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Aslantekin-Özçoban et al found that midwifery and nursing students had a moderate level of traumatic childbirth perception (mean, 64.26). 15 The most common traumatic events witnessed by students at childbirth were social or emotional: the woman's inability to cope with childbirth, use of verbal violence against the woman by health care professionals, and lack of emotional support to the woman by health care professionals. Physical traumas, such as maternal death, maternal resuscitation, and the dropping of the newborn, were found to be much less common.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations